“Pistol Fever”: Regulating Revolvers in Late-Nineteenth-Century Canada - Brown, Blake (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2009)
AbstractThis paper examines the debates over the regulation of pistols in Canada from confederation to the passage of nation’s first Criminal Code in 1892. It demonstrates that gun regulation has long been an important and contentious issue in Canada. Cheap revolvers were deemed a growing danger by the 1870s. A perception emerged that new forms of pistols increased the number of shooting accidents, encouraged suicide, and led to murder. A special worry was that young, working-class men were adopting pistols to demonstrate their manliness. Legislators responded to these concerns, but with trepidation. Parliament limited citizens’ right to carry revolvers, required retailers to keep records of gun transactions, and banned the sale of pistols to people under 16 years of age. Parliamentarians did not put in place stricter gun laws for several reasons. Politicians doubted the ability of law enforcement officials to effectively implement firearm laws. Some believed that gun laws would, in effect, only disarm the law abiding. In addition, a number of leading Canadian politicians, most importantly John A. Macdonald, suggested that gun ownership was a right of British subjects grounded in the English Bill of Rights, albeit a right limited to men of property.